An Analysis of Mediating Role of Entrepreneurial Self-Efficacy among Indian and Taiwanese University Students - Chang, Jen-Chia; Khan, Ehsan (Advances in Social Sciences Research Journal, 2023)
The purpose of this study is to explore the mediating effect of entrepreneurial self-efficacy (ESE) on the relationship between entrepreneurship education (EE) and the entrepreneurial intention (EI) of students belonging to the University of India and Taiwan also access the entrepreneurial self-efficacy level of India and Taiwan university students. The participants of this study included 299 university students (undergraduate and graduate) from India and Taiwan, the data was collected by online questionnaire survey circulated by mail. In the study, the researchers performed One-Way ANOVA, Correlation analysis, and Linear Regression analysis to check the hypothesis and at the end mediation analysis through “The process Macro” in SPSS software. The findings showed that: (1) there is no discernible difference between Indian and Taiwanese students' entrepreneurial intention (EI) features, and (2) Taiwanese students had greater levels of entrepreneurial self-efficacy than Indian university students. (3) Entrepreneurship education significantly impact the entrepreneurial intention and self-efficacy of the Indian and Taiwanese university. (4) The association between entrepreneurship education and entrepreneurial self-efficacy is significantly favorable, however, the relationship between entrepreneurship education and entrepreneurial intention is partially impacted by the mediating effect of entrepreneurial self-efficacy.